Perbandingan Sistem Pendidikan Islam Tradisional di Indonesia, Malaysia, dan Thailand - Alfyani Azzahroh; Alya Sukmasyariah; Hafizhotul Mumtazah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
This research aims to analyze and compare traditional Islamic education systems in Indonesia, Malaysia, and Thailand, focusing on institutional aspects, education systems, learning methods, and curricula. Using a literature study method with a descriptive qualitative approach, this research examines various relevant literature regarding the dynamics of Islamic education in Southeast Asia. The results show that the three countries share fundamental similarities in educational forms, such as pesantren or pondok, which focus on Islamic sciences and moral cultivation. However, significant differences exist in management patterns and the level of integration with government policies. Indonesia maintains a variety of salaf and modern pesantren, Malaysia exhibits a more structured system integrated with the state, while Thailand specifically in the Patani region tends to be adaptive in response to its Muslim minority status. This comparison concludes that the development of traditional Islamic education systems in each country is heavily influenced by the respective social and political contexts.